Study the etiopathogenesis and management of epistaxis - Rao, J. Sreenivasa; Rao, U. Srinivasa; Chandra, T. Sateesh (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2018)
Background: The aim of the study was to study the etiopathogenesis, age and sex distribution and management, chemical cautery, anterior and posterior nasal packing, nasal septal surgery, blood transfusion and arterial ligation. Methods: It is simple random sampling study undertaken to know the etiopathogenesis and management of epistaxis at government general hospital for 2 years. Results: The incidence of epistaxis was 1.5%. It was more in males with a male to female ratio of 1:9:1. The age incidence was more in the first and second decades and then increased from the fourth onwards with almost 60% cases belonging to this category. The seasonal incidence was more during cold, dry, winter months (70%). The commonest etiological factor was trauma (42%), followed by the hypertension (24%). 72% of patients had anterior nasal bleeding. The treatment options were divided onto non- surgical and surgical modalities. 86% of the patients were managed by conservative measures like medical treatment (42%) cautery (6%), anterior nasal packing (30%) and posterior nasal packing (4%). 14% of the patients required surgical intervention like septoplasty (2%), excision of bleeding nasal polypus (2%), nasal bone fracture reduction (2%), excision of adenoid cystic carcinoma of nose (2%), removal of rhinolith (92%), excision of angiofibroma of nose (4%). Conclusions: Anterior bleeding is more common and trauma is an important etiological factor. Majority cases of epistaxis are managable by conservative measures and only few require surgical intervention.